Public Ontologies about Electronic Government: a Systematic Literature Review - Pinto, Jaime Andrade; Almeida, Maurício Barcellos (Faculdade de Filosofia e Ciências, 2020)
In the context of construction and provision of Electronic Government services - eGov - it is important to advance in high-level modeling, seeking to represent knowledge about this domain. The problem presents itself as a question of generality and independence of the concepts involved. In the search for solutions, several academic and governmental initiatives seek consensus on government processes and the definition of their basic entities. In order for ontological models and system artifacts to be used reasonably independently of geographic boundaries, we need a definition and acceptance of everyone involved. In order to achieve this goal, it is necessary to have a broad consensus among designers, ease of use and flexibility of reuse and specialization. The objective of this work is to carry out a Systematic Literature Review on this subject and, presenting its findings, to direct future research. 236 studies were identified and, after applying exclusion criteria, 24 articles were analyzed. It was concluded that there are a reasonable number of models that can be reused, as they are in a good level of acceptance and international use.